2021
DOI: 10.1177/0963721421993820
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Emotion in Extreme Political Action: Individual Differences and Dynamic Interactions

Abstract: Who is most likely to join and engage in extreme political action? Although traditional theories have focused on situational factors or group identity, an emerging science illustrates that tendencies for extreme political action may also be rooted in individuals’ idiosyncratic cognitive and affective dispositions. This article synthesizes cutting-edge evidence demonstrating that individuals’ cognitive and affective architecture shapes their willingness to support ideological violence. In the cognitive domain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 40 publications
(44 reference statements)
0
23
0
Order By: Relevance
“…A recent investigation demonstrates that personality traits interact with the social context to shape citizens' social distancing behaviors during the COVID-19 pandemic (Ludeke, Vitriol, Larsen, & Gensowski, 2021), illustrating that context, geography, and personality dispositions can have joint and amplifying effects on each other. Acknowledging these (potentially non-linear) interactions is particularly important when we con sider real-life ideologically-motivated behavior such as extreme political action and violence (Zmigrod & Goldenberg, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation demonstrates that personality traits interact with the social context to shape citizens' social distancing behaviors during the COVID-19 pandemic (Ludeke, Vitriol, Larsen, & Gensowski, 2021), illustrating that context, geography, and personality dispositions can have joint and amplifying effects on each other. Acknowledging these (potentially non-linear) interactions is particularly important when we con sider real-life ideologically-motivated behavior such as extreme political action and violence (Zmigrod & Goldenberg, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of this work is that the effects of coherence and certainty cannot be disentangled from the one given by participants’ political extremity ( 11 , 17 , 19 ). This is because our measurement instruments do not allow us to define two similar levels of coherence or certainty with different extremity, or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…While interaction rules based on individuals rewarding similarity have been attributed as the main causes of the existence of echo chambers in social media ( 9 , 69 ) and the political segregation of societies ( 7 ), this work suggests that such an assumption may oversimplify the complexity of political interactions. Future research should examine whether and how the asymmetric effects reported in this work relate to emergent phenomena such as the extremification of political opinions ( 17 ), the polarization of beliefs ( 70 ), and the disappearance of moderate views ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be essential for a mature neurocognitive model of ideological behavior to address the neurocognitive impacts of both holding certain ideological beliefs (Connors & Halligan, 2015) and holding any belief to an extreme degree (Rollwage et al, 2019;Zmigrod, 2020b;Zmigrod & Goldenberg, 2021). Furthermore, as outlined in Figure 2C, the neurocognitive model explicitly postulates that there are bidirectional links between ideologies and neurocognitive processes, and so future research will need to untangle the causal arrows and cyclical effects between ideological and cognitive A neurocognitive model of ideological thinking POLITICS AND THE LIFE SCIENCES • FALL 2021 • VOL.…”
Section: Future Directionsmentioning
confidence: 99%